POTENSI MIKROORGANISME SEBAGAI AGEN BIOREMEDIASI MIKROPLASTIK DI LAUT - Milani Anggiani (OSEANA, 2020)
Microplastic is a threat to the survival of organisms on terrestrial and ocean. Microplastic waste accumulation from human activities will accumulate in the environment. The presence of microplastics in the environment is a problem because plastics are persistent. Plastics often contain chemicals that are potentially toxic and carcinogenic. They are consumed by organisms that will affect aquatic life. Plastic waste in the ocean will directly or indirectly poison the marine biota, damaging coral reefs which will further damage the balance of the marine ecosystem. The process of decomposition of plastic waste into microplastics takes hundreds of years through physical, chemical, and biological processes. The problem of microplastic waste can be overcome by biotechnology approaches. One of the strategies to control microplastic pollution is remediation technology by utilizing the potential of indigenous bacteria that grow in their natural environment. Furthermore, the use of bioremediation agents from other microorganisms has been carried out among them, using Fungi and Actinomycetes. The potential of microplastic degrading microorganisms in sea waters has not been done in depth, especially studies in improving the ability of microorganisms to degrade microplastics. The purpose of writing this review is to review the potential of microplastic degrading bacteria originating from marine waters.